2010
DOI: 10.1007/s11136-010-9733-2
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the medical outcomes study HIV (MOS-HIV) health survey among HIV-infected patients in Taiwan

Abstract: The findings of the present study provide strong evidence in support of the reliability and validity of the MOS-HIV health survey for the assessment of quality of life among HIV-infected patients in Taiwan. We find that the original factor structure of the MOS-HIV survey remains valid for patients from Chinese cultural backgrounds. This study therefore contributes to the existing evidence within the extant literature on the cultural relevance of the MOS-HIV health survey (a measure originally developed within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
2
8
0
2
Order By: Relevance
“…Firstly, ceiling effects were observed in six subscales, particularly in role functioning (71.1%), social functioning (63.2%), and pain (48.8%), while a floor effect was observed in role functioning (20.9%). The observed pattern of these effects (e.g., ceiling effects for role functioning, social functioning, and pain) is line with the results obtained from validation studies of the MOS-HIV in several languages [ 16 , 19 , 42 ]. For example, ceiling effects in role functioning (79%), social functioning (76%) and floor effect in role functioning (14.5%) were reported in the Thai version of the MOS-HIV [ 22 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Firstly, ceiling effects were observed in six subscales, particularly in role functioning (71.1%), social functioning (63.2%), and pain (48.8%), while a floor effect was observed in role functioning (20.9%). The observed pattern of these effects (e.g., ceiling effects for role functioning, social functioning, and pain) is line with the results obtained from validation studies of the MOS-HIV in several languages [ 16 , 19 , 42 ]. For example, ceiling effects in role functioning (79%), social functioning (76%) and floor effect in role functioning (14.5%) were reported in the Thai version of the MOS-HIV [ 22 ].…”
Section: Discussionsupporting
confidence: 85%
“…The ceiling effects observed in the present study might be related to the relatively good level of HIV-related condition of the participants, as evidenced by clinical characteristics such as 95.5% of the participants having CD4 cell counts of ≥200 cells/ml and 92% having an HIV RNA log value less than 40. In fact, majority of the participants in previous studies that reported similar patterns of ceiling or floor effects had CD4 cell counts of > 200 cells/ml [ 19 , 42 ]. On the other hand, floor effects in social functioning (21.2%) and role functioning (72.6%) were observed in the Italian version of the MOS-HIV [ 20 ], with only 7.6% of participants having CD4 cell counts of > 200 cells/ml [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary outcomes for parent measures included the number of participants who have disclosed their HIV serostatus to their children and participants' stage status regarding parental disclosure. Other key outcomes included perceptions and plans for parental disclosure, Derlega's scales on reasons for disclosure or non-disclosure, 30 Delaney's scale for child's reaction to the disclosure, 31 depressive symptoms (Center for Epidemiologic Studies Depression Scale (CES-D)), 32,33 stress (Perceived Stress Scale), 34 substance use (tobacco use, alcohol use (alcohol use disorders identification test (AUDIT)), 35 and other drug use), sexual behavior and reproductive health, HIV-related quality of life (Medical Outcomes Study HIV Health Survey (MOS-HIV)), 36 medical adherence (treatment history, knowledge about ART and adherence, and adherence to care and medications), and HIV clinical and immunologic status (most recent CD4 count, viral load, and disease progression).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Ainda que a aids seja considerada incurável, os avanços científicos no tratamento medicamentoso, pelo emprego da terapia antirretroviral de alta potência (TARV), proporcionaram significativo aumento da expectativa de vida do soropositivo ao HIV/com aids, que deixou de ser considerado portador de uma doença incurável, fatal e irreversível, tornando-se um indivíduo afetado por uma condição crônica potencialmente controlável (Bucciardini et al, 2006;Reis, 2008;Meirelles et al, 2010;Gaspar et al, 2011;Hsiung et al, 2011).…”
Section: Qualidade De Vida Relacionada à Saúde De Mulheres a Partir Dunclassified
“…Moçambique, Zâmbia e Botswana, se mostraram confiáveis e válidas para medir a QVRS de pessoas com HIV/aids, residentes nestas localidades (Taylor et al, 2009). (Holmes, Shea, 1997;Delate, Coons, 2000;García Ordóñez et al, 2001;Murri et al, 2003;Kohli et al, 2005;Perez et al, 2005;Nojomi, Anbary, Ranjbar, 2008;Hasanah, Zaliha, Mahiran, 2011;Hsiung et al, 2011); o uso de medicamentos antirretrovirais (García Ordóñez et al, 2001;Viswanthan, Anderson, Thomas, 2005;Mannheimer et al, 2005;Préau et al, 2006;Holmes et al, 2007;Valencia et al, 2010); maior tempo de conhecimento da infecção pelo HIV (Holmes, Shea, 1997;Globe, Hays, Cunninghan, 1999;Reis, 2008;Reynolds et al, 2009;Tsevat et al, 2009); e a percepção satisfatória do estado de saúde (Sousa et al, 1999;Phaladze et al, 2005 (Perez et al, 2005).…”
Section: Análise Logística Das Variáveis Independentes Selecionadas Cunclassified